2018
DOI: 10.1080/2162402x.2018.1440167
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling a CD70-positive subset of cancer-associated fibroblasts marked by pro-migratory activity and thriving regulatory T cell accumulation

Abstract: Cancer-associated fibroblasts (CAFs) are involved in the proliferative and invasive behavior of colorectal cancer (CRC). Nonetheless, CAFs represent a heterogeneous population with both cancer-promoting and cancer-restraining actions, lacking specific markers to target them. Expression of the immune checkpoint molecule CD70 is normally limited to cells of the lymphoid lineage. Instead, tumor cells hijack CD70 to facilitate immune evasion by increasing the amount of suppressive regulatory T cells (Tregs). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 53 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…Moreover, CAFs expressing CD70 enrich regulatory T cells to invasive colorectal cancer and CD70 expression is negatively correlated with survival of patients with colorectal cancer ( Fig. 1b) [47]. PDPN seems to be a potential therapeutic target while CD70 and vimentin might be more suitable for prognostic indicators and more evidences are warranted.…”
Section: Other Traditional Biomarkers: Pdgfr Vimentin Pdpn and Cd70mentioning
confidence: 95%
“…Moreover, CAFs expressing CD70 enrich regulatory T cells to invasive colorectal cancer and CD70 expression is negatively correlated with survival of patients with colorectal cancer ( Fig. 1b) [47]. PDPN seems to be a potential therapeutic target while CD70 and vimentin might be more suitable for prognostic indicators and more evidences are warranted.…”
Section: Other Traditional Biomarkers: Pdgfr Vimentin Pdpn and Cd70mentioning
confidence: 95%
“…These results all indicate that potential crosstalk between CAFs and Treg cells might exist. Evidence of the interaction between CD70 + CAFs and naturally occurring Tregs has already been reported [ 208 ]. In a study of colorectal cancer, researchers revealed that CAFs stimulate the migratory activity of Treg cells and markedly increase their frequency in tumor sites [ 208 ].…”
Section: Interaction Between Cafs and The Immune Microenvironment In Tumorsmentioning
confidence: 99%
“…In vitro studies show CD70 + CAFs isolated from invasive colorectal cancer specimens stimulate the migration of Tregs. Meanwhile, the expression of CD70 on CAFs is proved to be an independent adverse prognostic marker for colorectal cancer [113]. Bone marrow-derived CAFs can also inhibit allogeneic T cell responses through IDO production [114].…”
Section: Caf-related Anti-tumor Immune Responsementioning
confidence: 99%